Root surface caries among older Australians. Issue 6 (4th July 2018) - Hariyani, Ninuk; Spencer, A. John; Luzzi, Liana; Do, Loc Giang
Abstract: Objectives: Root caries has increased as a clinical problem in recent decades. However, the use of multiple waves of longitudinal follow‐up data in estimating root caries increment has not been previously attempted. The aims of this study were to quantify root caries increment from a longitudinal study of older adults with 4 oral examinations over 11 years and to examine behavioural factors associated with root caries. Methods: A secondary analysis was undertaken using data collected in 4 waves (baseline, 2‐year, 5‐year and 11‐year) of the South Australian Dental Longitudinal Study which began in 1991/92. The study group consisted of a stratified random sample of people aged 60+ years at baseline. A total of 358 participants with complete oral examinations in all 4 waves were included. The examinations were performed by trained and calibrated dentists. Baseline behavioural risk factors (toothbrushing frequency, flossing frequency, dental visiting pattern, reason for dental visiting and tobacco smoking status) and time in years across the 4 waves were the main exposures. Baseline clinical oral conditions (gingival condition and gingival recession), demographic and socio‐economic risk factors served as covariates. Root caries was measured as mean number of untreated root surfaces (root DS) and decayed/filled root surfaces (root DFS) at each wave of examinations. Multivariable multilevel growth model using linear regression analysis was used to get an estimate for root caries increment and associated oral health‐related behaviours adjusting for all the covariates. Results: Findings from the multivariable models indicated that the annual increment of root DS and root DFS were 0.07 (SE = 0.01) and 0.11 (SE = 0.02) surfaces, respectively. Irregular brushing (E [SE] = 0.25 [0.12]), visiting the dentist only for problems (E [SE] = 0.30 [0.13]) and smoking (E [SE] = 0.33 [0.12]) were risk factors for the increase in root DS. Irregular flossing and more frequent dental visit were associated with the increase in root DFS. Conclusions: Root caries increased slowly across time among relatively healthier Australian older adults. Irregular brushing, unfavourable dental visiting and tobacco smoking were risk factors for the increase in untreated root caries, while irregular flossing and more frequent dental visiting were associated with the increase in root DFS.